Effect of magnetic field treatment on the structural and aggregation behavior of gluten, gliadin, and glutenin in potato pulp enriched dough - Jialin Song; Feng Han; Ying Sun; Dongliang Zhang; Shanfeng Chen; Hongjun Li (Innovative Food Science & Emerging Technologies, 2026)

Extrusion-induced supramolecular disassembly of rice adjunct starch: governing enzymatic convertibility and fermentable sugar release in mashing - Lijun Jiang; Jialin Song; Mingming Qi; Jian Liu; Chengyi Sun; Bo Wang; Fengling Yue; Miaomiao Sui; Dongliang Zhang; Guihong Zhao; Hongjun Li (Food Chemistry, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Unregulated delayed emissions dominate ultrafine particles from modern diesel vehicles - Fuyang Zhang; Jianfei Peng; Peiji Liu; Yajun Wu; Jinsheng Zhang; Jiayuan Liu; Kexin Liu; Bin Sun; Qijun Zhang; Lin Wu; Ning Yang; Miao Tang; et al. (Journal of Hazardous Materials, 2026)

Spatiotemporal differences in traffic efficiency and CO2 emissions across day types: A city-level data-driven analysis of cooperative vehicle-infrastructure systems - Bin Sun; Haoyu Xu; Zhaolang Wu; Qijun Zhang; Lin Wu; Yan Liu; Yanan Mi; Hongjun Mao (Journal of Environmental Management, 2026)

Niche-specific and stage-dependent dynamics of microbial assemblages in the macroalgal cultivation system - Zhizhuo Shao; Xin Gao; Yi Sun; Yunlei Zhang; Hongjun Li (Regional Studies in Marine Science, 2026)

Measurement of interfacial wave velocity in swirling annular flow using array conductance sensor - Yanfeng Zhu; Chao Wang; Hongjun Sun (Chemical Engineering Journal, 2026)

How sea-land breezes affect ozone in coastal cities: spatial and temporal patterns - Naixiu Sun; Ya-nan Wang; Yu Fei; Lin Wu; Yicheng Yang; Liwei Li; Xueling Yang; Hongjun Mao (Environmental Monitoring and Assessment, 2026)

Impact of conservation tillage on maize growth dynamics in black soils of Northeast China through multi-platform remote sensing - Hongjun Liu; Junling Sun; Wei Wan; Shiwen Liu; Jianwei Li; Wei Lv; Zhong Liu (Field Crops Research, 2026)

Flow-induced vibration energy harvesting performance enhanced with convergent-acceleration effect - Hongjun Sun; Zeyao Yang; Jinxia Li; Zhen Yang (Ocean Engineering, 2026)

Bioaccumulation and trophic transfer of PAHs in the Yellow River Estuary food web: A fugacity-based model for ecological and human health risk assessment - Xin Liu; Xuguang Hong; Hongjun Song; Degang Wang; Kan Chen; Jiachen Sun; Zhaohui Zhang; Jiansong Chu (Marine Pollution Bulletin, 2026)

Interactions and binding mechanisms of soy protein isolate with theasinensin A in different pH conditions by multi-spectroscopy analysis and molecular docking - Haoyu Zhang; Weiqi Xu; Yulu Wang; Xia Fan; Qiankun Guo; Hongjun Liu; Jialu Ao; Tianjin Sun; Muhammad Abid; Xiaoxiong Zeng (Food Chemistry, 2026)

Novel anti-inflammatory peptides identified from beef tripe by network pharmacology, molecular docking, and in vitro study in RAW264.7 murine macrophages - Xuelian Sun; Zhifei He; Li Yang; Hongjun Li (Food Bioscience, 2026)

Quorum quenching driven enzymatic activity and metabolic pathway modulation in anaerobic reactor for enhanced methane production - Zijing An; Yibin Bao; Yuwei Yang; Xiaomei Su; Feng Dong; Xiao Xiao; Chongjun Chen; Hailu Fu; Hongjun Lin; Faqian Sun (Bioresource Technology, 2026)

Urbanization increases the impact of micropollutants on riverine planktonic food web - Bob Adyari; Lanping Zhang; Francisco J.A. Nascimento; Dandan Izabel-Shen; Yiqing Zhang; Meixian Cao; Jianjun Wang; Hongjun Li; Qian Sun; Chang-Ping Yu; Anyi Hu (Journal of Hazardous Materials, 2026)

The structure and performance of polyvinylidene fluoride membranes by using water-soluble polyester as an additive via immersion precipitation phase inversion - Jiaxin He; Shuo Sun; Hongjun Li; Wei Du; Hongwei Zhang; Danying Zuo (Journal of Fluorine Chemistry, 2026)

Evolving Collective Intelligence for Unmanned Marine Vehicle Swarms: A Federated Meta-Learning Framework for Cross-Fleet Planning and Control - Yuhan Ye; Hongjun Tian; Yijie Yin; Yuhan Zhou; Yang Xiong; Zi Wang; Yaojiang Liu; Zinan Nie; Zitong Zhang; Yichen Wang; Jingyu Sun (Journal of Marine Science and Engineering, 2025)
The development of robust autonomous maritime systems is fundamentally constrained by the “data silo” problem, where valuable operational data from disparate fleets remain isolated due to privacy concerns, severely limiting the scalability of general-purpose navigation intelligence. To address this barrier, we propose a novel Federated Meta-Transfer Learning (FMTL) framework that enables collaborative evolution of unmanned surface vehicle (USV) swarms while preserving data privacy. Our hierarchical approach orchestrates three synergistic stages: (1) transfer learning pre-trains a universal “Sea-Sense” foundation model on large-scale maritime data to establish fundamental navigation priors; (2) federated learning enables decentralized fleets to collaboratively refine this model through encrypted gradient aggregation, forming a distributed cognitive network; (3) meta-learning allows for rapid personalization to individual vessel dynamics with minimal adaptation trials. Comprehensive simulations across heterogeneous fleet distributions demonstrate that our federated model achieves a 95.4% average success rate across diverse maritime scenarios, significantly outperforming isolated specialist models (63.9–73.1%), while enabling zero-shot performance of 78.5% and few-shot adaptation within 8–12 episodes on unseen tasks. This work establishes a scalable, privacy-preserving paradigm for collective maritime intelligence through swarm-based learning.

Latitude-dependent diversity and assembly processes of coastal microbial communities across multiple trophic levels in the China Seas - Yunlei Zhang; Xin Gao; Zhizhuo Shao; Yi Sun; Zheng Zhang; Hongjun Li; Jinqing Ye (Frontiers in Marine Science, 2025)
Coastal sediment ecosystems function as dynamic interfaces for land-sea interactions, harboring highly complex microbial communities which support vital ecological functions. However, the mechanisms governing microbial diversity maintenance and cross-trophic community assembly at large spatial scales remain poorly explored. In this study, a high-throughput sequencing approach was employed to analyze the bacterial, fungal and protistan communities in surface sediments of the China Seas. As indicated by higher values across most indices, bacterial communities generally exhibited greater richness and alpha diversity compared to fungal and protistan communities. Beta diversity decomposition revealed that species turnover dominated community variations across all three trophic levels, with the highest contribution in bacteria. The neutral community model revealed that stochastic processes exerted a stronger influence on bacterial assembly relative to fungi and protists. Moreover, null model analyses demonstrated that bacterial communities were primarily structured by dispersal limitation, fungal communities by ecological drift, while protistan communities co-regulated by homogeneous selection and homogenizing dispersal. Furthermore, similar latitude-dependent patterns in the α- and β- diversity were observed in bacteria and protists, yet such patterns were distinct for fungi. Finally, based on the correlations between community variations with their assembly mechanisms, regional species pools exerted the strongest influence on bacterial β-diversity, whereas local assembly processes dominated fungal β-diversity. The present study elucidates the trophic-level-dependent assembly rules of coastal microbiomes, thereby establishing a mechanistic foundation for predicting ecosystem responses to global change and informing evidence-based conservation of coastal ecosystems.

Tunable surface potential nanomaterials for enhanced environmental nucleic acid extraction and surveillance - Jiahui Lv; Tong Li; Ying Liu; Bing Li; Peng Jia; Chuwei Ma; Hongjun Xiao; Guanghui Wang; Li Cheng; Jingkai Yang; Ziyi Xu; Xuan Tan; et al. (Water Research, 2025)

The sedimentary provenance of Upper Miocene Dongfang submarine fan, Yinggehai Basin: source-to-sink system unravelled through new detrital zircon U-Pb ages and heavy mineral analysis - Xingzong Yao; Congjun Feng; Wei Zhou; Pengfei Wu; Hongjun Qu; Jiahao Lei; Zhiqiang Chen; Yanlong Ge; Mengsi Sun (Marine and Petroleum Geology, 2025)

Ultrasound-assisted fermentation of doughs enriched with 7S and 11S soy protein fractions: impacts on quality and protein–protein interactions - Feng Han; Ying Sun; Jialin Song; Xin Zhang; Chuangshuo Yan; Yufan Wang; Shanfeng Chen; Chengye Ma; Hongjun Li (Food Research International, 2025)

Pulse electrodeposition of graphene/copper composite foils from waste printed circuit board leachate - Yan Sun; Yamin Li; Jingyu Zhang; Hongjun Liu (Chemical Engineering Journal, 2025)

MAZ-mediated LAMA5 transcription activation promotes gastric cancer progression through the STAT3 signaling - Yu Wang; Jiazhong Xu; Hongxia Zhang; Xiaobo Guo; Hongjun Liu; Qinhui Sun (Functional & Integrative Genomics, 2025)

Evaluation of feeding intensity in pearl gentian grouper under factory aquaculture environment based on multi-feature fusion and MDGSNet model - Zeshuang Ma; Hongpo Wang; Hong Zhou; Yunchen Tian; Jianing Quan; Haohui Liu; Zhanshuo Sun; Hongjun Yang (Aquaculture International, 2025)

Characterizations of air pollutants at roadside monitoring stations and traffic emission effects: A case study in Tianjin, China - Fangyuan Zheng; Junxia Gao; Lin Wu; Naixiu Sun; Wentian Xu; Qijun Zhang; Hongjun Mao; Jianfei Peng; Liwei Li; Ning Yang; Bin Liu (Journal of Environmental Sciences, 2025)

Widely targeted metabolomics and GC–IMS reveal flavor and metabolite variations in Rex and Hyla rabbit meat under different cooking methods - Shuyun Liu; Hongjun Li; Bin Wen; Li Yang; Xuelian Sun; Kaitong Lang; Zhifei He (Food Chemistry, 2025)

Biotransformation and toxicity attenuation of 2,6-Dichlorobenzoquinone in simulated human gastrointestinal conditions: Insights from a systematic in vitro study - Lili Zheng; Guolong Chen; Kuangtao Fu; Zhen Wang; Xinyue Yuan; Hongjie Sun; Wenjing Deng; Zeqiong Xu; Hongjun Lin; Huachang Hong (Journal of Hazardous Materials, 2025)

Sustainable impact of urban road class on smart transportation systems: A field data-informed exploration - Bin Sun; Qiang Bai; Qijun Zhang; Hongjun Mao (Sustainable Cities and Society, 2025)

Excess vehicular evaporative emissions for prolonged parking during the COVID-19 lockdown in China - Pengfei Song; Jianfei Peng; Yan Liu; Chongzhi Zhong; Qiang Chen; Chao Zou; Shida Sun; Yajun Wu; Yao Gu; Taiyu Zhang; Ning Yang; Hongjun Mao (Journal of Hazardous Materials, 2025)

Declining floral color diversity alters bee color preferences in fragmented habitats - Hongjun Xie; Peng Ren; Chen Zhu; Juan Liu; Minghao Sun; Xingfeng Si; Ping Ding (Biological Conservation, 2025)

Multi-perspective analysis of long-term vehicle emissions under intensive policy updates in China - Wentian Xu; Fangyuan Zheng; Zhouzhi Li; Junxia Gao; Hui Tong; Haomiao Niu; Bin Sun; Zhaoyang Fan; Lin Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2025)

Rice-fish coculture without phosphorus addition improves phosphorus availability in paddy soil by regulating phosphorus fraction partitioning and alkaline phosphomonoesterase-encoding bacterial community - Xing LIU; Yuting CHEN; Hongjun ZHENG; Daolin SUN; Jiaen ZHANG; Qi JIA; Qi CHEN (Pedosphere, 2025)

Cu-Thioamide coordination polymers derived Cu-S catalysts for CO2 electroreduction to formate - Honglin Li; Xin Zhang; Yuanyuan Wen; Jingyuan Li; Yu Liu; Hongjun Mao; Hongman Sun; Jingbin Zeng; Zifeng Yan (Fuel, 2025)

Direct visual detection for methicillin-resistant Staphylococcus aureus in milk based on the RPA-Cas12a-LFS method - Yixiang Sun; Liren Zhang; Huimin Wu; Hongjun Chen; Huijie Hu; Chongyu Zhang; Xiaoqiang Li; Yuan Li; Yimai Wang; Liqiang Luo; Yizhi Song (Food Control, 2025)

Optimizing Lancang-Mekong hydropower portfolio effectively reduces greenhouse gas emissions - Xiaobo Yun; Qiuhong Tang; Jie Wang; Siao Sun; Hongjun Bao; Yadu Pokhrel; Lifeng Luo; Deliang Chen (Environmental Impact Assessment Review, 2025)

RBM15-mediated m6A modification of XPR1 promotes the malignant progression of lung adenocarcinoma - Changpeng Sun; Hongjun Guan; Jinjin Li; Yinfeng Gu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Environmental benefit assessment of vehicle electrification in the fuel cycle: A case study of Chengdu - Zhaoyang Fan; Hui Tong; Naixiu Sun; Yangxin Xiong; Xuan Qu; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

Aerated Drip Irrigation: A Sustainable Approach to Improving Soil Environment, Crop Growth, Quality, and Yield in Greenhouse Cultivation - Yecheng Dong; Hongjun Lei; Zheyuan Xiao; Cuicui; Jin; Yingji Lian; Hongwei Pan; Zhengjun Zhang; Chen Yin; Keping Sun (Journal of Soil Science and Plant Nutrition, 2025)

A synergistic approach integrating potassium ferrate oxidation with polyacrylamide flocculation to enhance sludge dewatering and its mechanisms - Yansha Zeng; Yue Shen; Hongjun Lin; Qiyin Tan; Jiahao Sun; Liguo Shen; Renjie Li; Yanchao Xu; Jiaheng Teng (Journal of Environmental Management, 2025)

Functional characterization of a lytic polysaccharide monooxygenase EbLPMO10A that contributes to β-chitin degradation by chitinase - Haipeng Su; Chaoran Guo; Hongjun Zhao; Hao Dong; Jianan Sun; Xiangzhao Mao (Food Chemistry, 2025)

FePS3-Nanosheets-Integrated multifunctional nanocomposite hydrogel for multimodal synergistic osteosarcoma therapy and enhanced bone regeneration - Bing Ye; Xirui Jing; Yanlin Su; Wenzhe Sun; Qing Gao; Lian Zeng; Hongwei Lu; Shuo Tang; Yizhou Wan; Tingfang Sun; Zekang Xiong; Xiao Lv; et al. (Chemical Engineering Journal, 2025)

Contribution of Vehicular Evaporative S/IVOC emission to SOA formation in China - Zhaoyang Fan; Yajun Wu; Yuwei Xie; Hui Tong; Naixiu Sun; Pengfei Song; Wentian Xu; Yan Liu; Shaojie Song; Hongjun Mao; Jianfei Peng (Atmospheric Environment, 2025)

Correction: Thioredoxin-1 Protects Neurons Through Inhibiting NLRP1-Mediated Neuronal Pyroptosis in Models of Alzheimer’s Disease - Jinjing Jia; Hongjun Liu; Liyan Sun; Yunfeng Xu; Xiansi Zeng (Molecular Neurobiology, 2025)

Correction: Thioredoxin-1 Protects Neurons Through Inhibiting NLRP1-Mediated Neuronal Pyroptosis in Models of Alzheimer’s Disease - Jinjing Jia; Hongjun Liu; Liyan Sun; Yunfeng Xu; Xiansi Zeng (Molecular Neurobiology, 2025)

Risk-based environmental assessment of atmospheric impact in the hydrometallurgical recycling of LFP batteries: A comparative analysis of operational scenarios - Yunbin Sun; Zaohong Zhou; Hongjun He; Qiang Li (Journal of Cleaner Production, 2025)

Effect of cooking treatment on protein digestibility, peptide profile and potential bioactive peptides of beef tripe during in vitro gastrointestinal digestion - Xuelian Sun; Zhifei He; Li Yang; Hongjun Li (Food Chemistry, 2025)

Green β-cyclodextrin interlayered crumpled polyamide membranes for effective desalination - Jian Yu; Ling Zhang; Hongguang Sun; Renjie Li; Die Ling Zhao; Liguo Shen; Hongjun Lin; Yang Jiao; Yanchao Xu (Desalination, 2025)

High-Probability Ground Motion Simulation in Maduo County for the Maduo MS7.4 Earthquake in 2021: A Possible Supershear Earthquake - Zongchao Li; Zhiwei Ji; Jize Sun; Hiroe Miyake; Yanna Zhao; Hongjun Si; Mengtan Gao; Yi Ding (Journal of Earth Science, 2025)

Multifactorial Controls on the Dongdaobei Submarine Canyon System, Xisha Sea, South China Sea - Meijing Sun; Hongjun Chen; Chupeng Yang; Xiaosan Hu; Jie Liu (Journal of Marine Science and Engineering, 2025)
The submarine canyons system is the most widely distributed geomorphic unit on the global continental margin. It is an important concept in the field of deep-water sedimentation and geohazards. Based on high-resolution multibeam bathymetry and two-dimensional seismic data, the dendritic canyon system north of Dongdao island is studied at the eastern Xisha area of the South China Sea. The Dongdaobei submarine canyon is distributed in water depths between 1000 and 3150 m. The main source area in the upper course of the canyon originates from the northwest of Dongdao platform and the Yongxing platform. The sediments from the source area are transported to the main canyon in the form of various gravity flows. Landslides on the slope significantly impact canyon evolution by delivering sediment to the canyon head and causing channel deflection through substrate failure and flow-path reorganization. A large number of pockmarks are distributed around the north slope of the main canyon. The small-scale channels, which are formed as a result of the continuous erosion of the pockmark chains, are connected to the canyon sidewalls. The seamounts are distributed along the south bank of the canyon, exerting a controlling influence on the directional changes in the main canyon’s downstream segment. The formation and evolution of the Dongdaobei submarine canyon are primarily influenced by several factors, including tectonic activity and inherited negative topography, erosion by sedimentary gravity flows, sediment instability, and the shielding effect of seamounts.

Corrigendum to ‘Exploring the maximum nitrite production rate through the granular sludge-type reactor to match the needs of anammox process realizing efficient nitrogen removal’ [Environ. Res. 255 (2024) 119158] - Hongjun Zhao; Yan Guo; Xiaona Wang; Haishu Sun; Ming Gao; Chuanfu Wu; Shuang Li; Yu-you Li; Qunhui Wang (Environmental Research, 2025)

A single-atom manganese nanozyme mediated membrane reactor for water decontamination - Jiahao Sun; Minjia Yan; Guangdong Tao; Runbin Su; Xuanming Xiao; Qiangshun Wu; Feng Chen; Xi-Lin Wu; Hongjun Lin (Water Research, 2025)

Novel insights into halogenated carbazoles (HCZs) prediction in tap water: A comparative study of grey relational analysis-based neural networks - Qianfeng He; Wanting Xu; Guolong Chen; Zhen Wang; Yan Liang; Hongjie Sun; Huachang Hong; Hongjun Lin; Zeqiong Xu (Journal of Cleaner Production, 2025)

Astral-based DIA proteomics explored the flavor enhancement mechanism of Chinese traditional smoked bacon by staphylococcal co-fermentation - Li Yang; Hongjun Li; Han Wu; Xueling Sun; Shuyun Liu; Kaitong Lang; Zhifei He (Food Chemistry, 2025)

Effect of Photoperiod on Nutritional Quality of Muscle and Lipid Metabolism of Litopenaeus vannamei - Yingying Fang; Fan Fei; Fulu Guo; Chengliang Zhu; Xiaoqiang Gao; Wenyang Li; Hongjun Yang; Yan Sun; Chuanxin Zhang; Baoliang Liu (Fishes, 2024)
Photoperiod serves as a significant environmental signal for organisms and plays a critical role in regulating their metabolic processes. This research aimed to investigate the lipid metabolism and nutritional quality of adults Litopenaeus vannamei (wet weight: 11.27 ± 0.73 g, body length: 12.45 ± 0.42 cm) under five photoperiods (0L:24D, 8L:16D, 12L:12D, 16L:8D, and 24L:0D) for 40 days in recirculating water systems (RASs). The 24L:0D group increased lipid metabolism, as indicated by increased lipid metabolism enzyme levels and related gene expression linked to lipogenesis. Additionally, shrimp in the 24L:0D exhibited the highest value of crude fat. The 0L:24D showed a significantly reduced content of crude fat compared with the 8L:16D and 12L:12D. In 24L:0D, the content of total essential amino acids (TEAAs), total hydrolyzed essential amino acids (THEAAs), and total non-essential amino acids (TNEAAs) increased significantly. Similarly, the content of polyunsaturated fatty acids (PUFAs) in 24L:0D was also higher than in other groups. Conversely, 0L:24D resulted in lower metabolic activity and a reduction in PUFA content. In conclusion, prolonging light could benefit shrimp cultivation. This study thoroughly examined the effects of varying photoperiods on muscle quality and lipid metabolism in L. vannamei, providing essential insights for the improvement of indoor aquaculture environments. Provision of light for 24 h improves production but has some adverse effects on animal welfare, so a 16 h light cycle is recommended.

Can transportation networks contribute to the sustainable development of urban agglomeration spatial structures? - Xueqing Sun; Pengcheng Xiang; Dong Ngoduy; Hongjun Sui; Bo Zhang (Sustainable Cities and Society, 2024)

Membrane fouling characteristics and mechanisms in coagulation-ultrafiltration process for treating microplastic-containing water - Yue Shen; Qiyin Tan; Jiahao Sun; Xiang Cai; Liguo Shen; Hongjun Lin; Xiaoxuan Wei (Science of The Total Environment, 2024)

Drought risk assessment for maize/peanut intercropping based on crop model and SPEI - Yajiaoxue Guo; Zhanxiang Sun; Wei Bai; Zhe Zhang; Yue Zhang; Hongjun Du; Tianran Sun; Jinyu Zhang; Pu Peng; Yafei Ji; Qian Cai; Zhi Dong; et al. (Agricultural Systems, 2024)

Impacts of traffic-signal-based speed guidance system across different application stages on traffic - Bin Sun; Le Hu; Qijun Zhang; Chao Zou; Ning Wei; Zhenyu Jia; Zhong Wu; Hongjun Mao (Transportation Research Part D: Transport and Environment, 2024)

Effects of calcium ions and polysaccharides type on transparent exopolymer particle formation and the related fouling mechanisms - Qiyin Tan; Yue Shen; Jiahao Sun; Tao Jian; Wen Lu; Sijin Wu; Zengjian Zhao; Qian Lei; Hongjun Lin (Science of The Total Environment, 2024)

Activation of peroxymonosulfate by novel magnetically recyclable CoFe2O4/MXene quantum dots composites for rapid degradation of tetracycline: Synergistic performance and mechanisms - Zhenyu Guo; Haiyi Jin; Hongyu Sun; Bisheng Li; Huadong Yu; Die Ling Zhao; Hongjun Lin (Journal of Environmental Management, 2024)

Efficient nitrogen removal and stable operation of a dynamic membrane bioreactor (DMBR) for landfill leachate treatment - Jie Han; Wei Xu; Junjie Zhu; Xiaomei Su; Hailu Fu; Xiao Xiao; Feng Dong; Chongjun Chen; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2024)

Thioredoxin-1 Protects Neurons Through Inhibiting NLRP1-Mediated Neuronal Pyroptosis in Models of Alzheimer’s Disease - Jinjing Jia; Hongjun Liu; Liyan Sun; Yunfeng Xu; Xiansi Zeng (Molecular Neurobiology, 2024)

Response of food waste anaerobic digestion to the dimensions of micron-biochar under 30 g VS/L organic loading rate: Focus on gas production and microbial community structure - Qiang Liu; Ziyan Sun; Junting Pan; Lu Feng; Hongjun Zhou; Yeqing Li; Gang Li (Chemosphere, 2024)

An energy-based framework for predicting vehicle noise source intensity: From energy consumption to noise - Bin Sun; Haibo Wang; Qijun Zhang; Hanchao Shi; Hongjun Mao (Journal of Environmental Management, 2024)

Microcellular foaming-derived strong ultra-high molecular weight polyethylene/high-density polyethylene foams for thermally insulating and oil-water separating applications - Xujiang Sun; Guilong Wang; Zhaorui Xu; Jialong Chai; Aimin Zhang; Guoqun Zhao; Shuai Li; Yupeng Wang; Hongjun Jiao (Journal of Environmental Chemical Engineering, 2024)

Flotation-assisted electrodeposition process to recover copper from waste printed circuit boards - Yamin Li; Xuehao Wei; Hongjun Liu; Yan Sun (Chemical Engineering Journal, 2024)

Enhanced sludge dewatering using a novel synergistic iron/peroxymonosulfate-polyacrylamide method - Yansha Zeng; Zhe Wang; Qiyin Tan; Yue Shen; Jiahao Sun; Liguo Shen; Jiaheng Teng; Hongjun Lin (Journal of Environmental Management, 2024)

New insights into the dominance of mixed fermentation of Staphylococcus cohnii and Staphylococcus saprophyticus in Chinese bacon: Complete genomic and comparative genomic perspectives - Li Yang; Hongjun Li; Han Wu; Xuelian Sun; Shuyun Liu; Dong Zhang; Chang Su; Zhifei He (Food Research International, 2024)

Quantitative proteomic analysis to identify potential biomarkers linked to quality traits of beef tripe from different sources - Xuelian Sun; Zhifei He; Li Yang; Han Wu; Hongjun Li (Food Chemistry, 2024)

Exploring the maximum nitrite production rate through the granular sludge-type reactor to match the needs of anammox process realizing efficient nitrogen removal - Hongjun Zhao; Yan Guo; Xiaona Wang; Haishu Sun; Ming Gao; Chuanfu Wu; Shuang Li; Yu-you Li; Qunhui Wang (Environmental Research, 2024)

Quantitative trait locus analysis of gray leaf spot resistance in the maize IBM Syn10 DH population - Lina Cui; Mingfei Sun; Lin Zhang; Hongjie Zhu; Qianqian Kong; Ling Dong; Xianjun Liu; Xing Zeng; Yanjie Sun; Haiyan Zhang; Luyao Duan; Wenyi Li; et al. (Theoretical and Applied Genetics, 2024)

Interdecadal Change of the Relationship between Early Summer Precipitation over Northeast China and Spring Land Surface Thermal Anomalies in West Asia - Hongjun Sun; Haishan Chen; Xinguan Du; Yinshuo Dong (Journal of Meteorological Research, 2024)

How temporary disruption of metro service influence metro commuters’ mode shifts during the COVID-19 pandemic? Evidence from Tianjin, China - Xinwei Ma; Shaofan Sun; Lin Li; Mingjia He; Hongjun Cui (Travel Behaviour and Society, 2024)

Rice-fish coculture without phosphorus addition improves paddy soil nitrogen availability by shaping ammonia-oxidizing archaea and bacteria in subtropical regions of South China - Xing Liu; Daolin Sun; Huaqiao Huang; Jiaen Zhang; Hongjun Zheng; Qi Jia; Min Zhao (Science of The Total Environment, 2024)

Contrasting benthic bacterial and fungal communities in two temperate coastal areas affected by different levels of anthropogenic pressure - Zhen Wang; Xiaohan Liu; Xiaocheng Wang; Haining Wang; Yi Sun; Jinyong Zhang; Hongjun Li (Marine Environmental Research, 2024)

Unveiling long-term combined effect of salinity and Lead(II) on anammox activity and microbial community dynamics in saline wastewater treatment - Wenjun Yin; Yilin Li; Wei Xu; Yibin Bao; Junjie Zhu; Xiaomei Su; Jie Han; Chongjun Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2024)

Exploring vehicle-centric strategies for sustainable urban mobility: A theoretical framework for saving energy and reducing noise in transportation - Bin Sun; Haibo Wang; Le Hu; Qijun Zhang; Hanchao Shi; Hongjun Mao (Journal of Environmental Management, 2024)

Atmospheric environment characteristic of severe dust storms and its impact on sulfate formation in downstream city - Naixiu Sun; Lin Wu; Fangyuan Zheng; Danni Liang; FuYuan Qi; Shaojie Song; Jianfei Peng; Yufen Zhang; Hongjun Mao (Science of The Total Environment, 2024)

Xenocrystic zircons from mafic volcanic rocks in the Bikou Terrane: A window to trace the Paleoarchean to Mesoproterozoic crustal evolution of the northwestern Yangtze Block, South China - Bo Hui; Yunpeng Dong; Hongjun Qu; Shengsi Sun; Franz Neubauer; Feifei Zhang; Rutao Zang; Shuxuan Yan; Guiyun Wang (Precambrian Research, 2024)

Emerging disinfection byproducts 3-bromine carbazole induces cardiac developmental toxicity via aryl hydrocarbon receptor activation in zebrafish larvae - Yingying Liu; Xudong Jin; Yanan Ye; Zeqiong Xu; Zhongkun Du; Huachang Hong; Haiying Yu; Hongjun Lin; Xianfeng Huang; Hongjie Sun (Environmental Pollution, 2024)

Residues of Polycyclic Aromatic Hydrocarbons in Breast Milk Collected from Jinhua (China) and the Influence of Exercise Habit: Levels and the Potential Health Effects - Qianfeng He; Xiaoge Zhang; Lihong Kuang; Haotian Xu; Yizhong Hou; Fangqu Huang; Zeqiong Xu; Hongjie Sun; Wenjing Deng; Hongjun Lin; Huachang Hong (Exposure and Health, 2024)

New directions on membranes for removal and degradation of emerging pollutants in aqueous systems - Die Ling Zhao; Wangyi Zhou; Liguo Shen; Bowen Li; Hongyu Sun; Qianqian Zeng; Chuyang Y. Tang; Hongjun Lin; Tai-Shung Chung (Water Research, 2024)

Pathogenicity and horizontal transmission evaluation of a novel isolated African swine fever virus strain with a three-large-fragment-gene deletion - Han Gao; Dongdong Di; Qianwen Wu; Jie Li; Xing Liu; Zhiying Xu; Sijia Xu; Chengyu Wu; Lang Gong; Yankuo Sun; Guihong Zhang; Hongjun Chen; et al. (Veterinary Microbiology, 2024)

Regenerative braking system effectively reduces the formation of brake wear particles - Qijun Zhang; Jiawei Yin; Tiange Fang; Quanyou Guo; Jiaxing Sun; Jianfei Peng; Chongzhi Zhong; Lin Wu; Hongjun Mao (Journal of Hazardous Materials, 2024)

New insights into survival strategies and PCB bioremediation potential of resuscitated strain Achromobacter sp. HR2 under combined stress conditions - Jie Shi; Yingying Yang; Shusheng Zhang; Qihua Lin; Faqian Sun; Hongjun Lin; Chaofeng Shen; Xiaomei Su (Journal of Hazardous Materials, 2024)

Novel combination of iron-carbon composite and Fenton oxidation processes for high-concentration antibiotic wastewater treatment - Zhe Wang; Yansha Zeng; Qiyin Tan; Yue Shen; Liguo Shen; Jiahao Sun; Leihong Zhao; Hongjun Lin (Journal of Environmental Management, 2024)

Unveiling the PCB biodegradation potential and stress survival strategies of resuscitated strain Pseudomonas sp. HR1 - Yingying Yang; Qian Zhang; Qihua Lin; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Environmental Pollution, 2024)

Evaluation indicators for road traffic energy consumption: a review and prospect - Bin Sun; Le Hu; Zhaoyang Fan; Hongjun Mao; Qijun Zhang (Environmental Science and Pollution Research, 2024)

Environmental impacts of potential mining-replacing-import alternative for China in response to the China-Australia coal ban - Zhaoyang Fan; Xin Ju; Hui Tong; Zilu Liang; Naixiu Sun; Hongjun Mao; Jianfei Peng (Journal of Cleaner Production, 2024)

Assembly mechanisms of microbial communities in plastisphere related to species taxonomic types and habitat niches - Yi Sun; Hongjun Li; Jinyong Zhang; Haining Wang; Xiaoyu Cui; Xin Gao; Wenwen Qiao; Yuyi Yang (Marine Pollution Bulletin, 2024)

The stable operation of nitritation process with the continuous granular sludge-type reactor and microbial community analysis - Hongjun Zhao; Yan Guo; Ze Zhang; Haishu Sun; Xiaona Wang; Shuang Li; Jianbo Liao; Yu-You Li; Qunhui Wang (Chemosphere, 2023)

Anaerobic biodegradation of azo dye reactive black 5 by a novel strain Shewanella sp. SR1: Pathway and mechanisms - Jiale Liu; Lu Fan; Wenjun Yin; Shusheng Zhang; Xiaomei Su; Hongjun Lin; Haiying Yu; Zhenghai Jiang; Faqian Sun (Journal of Environmental Management, 2023)

Unlocking the potential of resuscitation-promoting factor for enhancing anaerobic microbial dechlorination of polychlorinated biphenyls - Zhen Han; Aiqin Hou; Xiaolin Cai; Mengqi Xie; Faqian Sun; Chaofeng Shen; Hongjun Lin; Haiying Yu; Xiaomei Su (Science of The Total Environment, 2023)

Benthic bacterial communities indicate anthropogenic activity footprints in coastal area under long-term marine spatial planning practice - Yi Sun; Hongjun Li; Daixi Liu; Xiaocheng Wang; Quanming Wang; Xiaoyu Cui; Jingfeng Fan (Acta Oceanologica Sinica, 2023)

The combination of multiple linear regression and adaptive neuro-fuzzy inference system can accurately predict trihalomethane levels in tap water with fewer water quality parameters - Jianzhen Zhang; Duo Ye; Quanyou Fu; Minjie Chen; Hongjun Lin; Xiaoling Zhou; Wenjing Deng; Zeqiong Xu; Hongjie Sun; Huachang Hong (Science of The Total Environment, 2023)

Anaerobic biodegradation of anthraquinone dye reactive black 19 by a resuscitated strain Bacillus sp. JF4: Performance and pathway - Qian Zhang; Yuyang Wang; Mayada Jamal; Rui Wang; Qiuyang He; Faqian Sun; Hongjun Lin; Xiaomei Su (Journal of Environmental Chemical Engineering, 2023)

Enhanced methane yield in anaerobic digestion of waste activated sludge by combined pretreatment with fungal mash and free nitrous acid - Min Zhang; Yuwei Yang; Huaqian Mou; Aodong Pan; Xiaomei Su; Jianrong Chen; Hongjun Lin; Faqian Sun (Bioresource Technology, 2023)

Seasonal implications for taxonomic sufficiency to simplify M-AMBI methodology in the coastal area adjacent to a eutrophic estuary - Chenman Yang; Hongjun Song; Yi Sun; Pengfei Xie; Yuan Liu; Hongjun Li (Acta Oceanologica Sinica, 2023)

Evaluating vehicular exhaust and evaporative emissions via VOC measurement in an underground parking garage - Yajun Wu; Yan Liu; Peiji Liu; Luna Sun; Pengfei Song; Jianfei Peng; Ruikang Li; Ning Wei; Lin Wu; Ting Wang; Lina Zhang; Ning Yang; et al. (Environmental Pollution, 2023)

Clinical, epidemiological, and genotypic characteristics of rotavirus infection in hospitalized infants and young children in Yunnan Province - Hongjun Jiang; Yu Zhang; Xiaoyan Xu; Xiaohan Li; Yi Sun; Xin Fan; Ya Xu; Ting Su; Guiqian Zhang; Ziqin Dian (Archives of Virology, 2023)
Rotaviruses are the most important pathogenic cause of non-bacterial diarrhea in infants and children. Approximately 60% of hospital admissions for acute diarrhea worldwide are caused by rotavirus infection. Rotavirus infection and hospitalization among children in China are a social burden, resulting in economic loss. The prevalence and geographical distribution of rotavirus genotypes is variable, partially due to population migration. Due to the unique geographical conditions and climate in Yunnan Province, several viruses with new genotypes have emerged, and multiple genotypes have become co-epidemic. In this study, rotavirus infection screening and genetic characterization of epidemic strains were performed in 149,492 infants and children admitted to hospitals in six representative prefectures in Yunnan Province between 2019 and 2021. The prevalence of rotavirus infection was 13.39% and was highest in January and lowest in September. G9P[8] was the main epidemic rotavirus genotype. Other epidemic genotypes included G2P[4], G8P[8], G9P[4], G2P[8], G3P[8], G4P[8], G3P[4], and G4P[6]. Phylogenetic analysis revealed that locally epidemic strains were influenced by importation of strains from neighboring provinces and other Asian countries. These findings provide a scientific basis for rotavirus prevention and control and lay a foundation for preliminary studies to establish a rotavirus surveillance network in Yunnan Province.

Material efficiency strategies across the industrial chain to secure indium availability for global carbon neutrality - Huiling Song; Chang Wang; Kun Sun; Hongjun Geng; Lyushui Zuo (Resources Policy, 2023)

Effect of quorum quenching on biofouling control and microbial community in membrane bioreactors by Brucella sp. ZJ1 - Rui Wang; Zijing An; Lu Fan; Yan Zhou; Xiaomei Su; Junjie Zhu; Qian Zhang; Chongjun Chen; Hongjun Lin; Faqian Sun (Journal of Environmental Management, 2023)

Phenol degradation at high salinity by a resuscitated strain Pseudomonas sp. SAS26: kinetics and pathway - Shusheng Zhang; Zijing An; Xiaomei Su; Aiqin Hou; Leilei Liu; Lihua Zhang; Qiuyang He; Faqian Sun; Zupei Lei; Hongjun Lin; Jiahou Lai (Journal of Environmental Chemical Engineering, 2023)

Anaerobic membrane bioreactor for the treatment of high-strength waste/wastewater: A critical review and update - Zijing An; Junjie Zhu; Min Zhang; Yan Zhou; Xiaomei Su; Hongjun Lin; Faqian Sun (Chemical Engineering Journal, 2023)

Bibliometric analysis and mini-review of global research on pyroptosis in the field of cancer - Wenwen Wang; Wenhuizi Sun; Han Xu; Yao Liu; Chenlu Wei; Siqiao Wang; Shuyuan Xian; Penghui Yan; Jiajun Zhang; Hongjun Guo; Hengwei Qin; Jie Lian; et al. (Apoptosis, 2023)

Comparation of mesophilic and thermophilic anaerobic co-digestion of food waste and waste activated sludge driven by biochar derived from kitchen waste - Rong Zhang; Min Zhang; Huaqian Mou; Zijing An; Hailu Fu; Xiaomei Su; Chongjun Chen; Jianrong Chen; Hongjun Lin; Faqian Sun (Journal of Cleaner Production, 2023)

Characterization and phylogenetic analysis of bovine gammaherpesvirus 4 isolated in China, 2022 - Weiqiang Guo; Tong Sun; Yingnan Liu; Xulai Duan; Chuanwen Tian; Zhou Zhou; Yong-Sam Jung; Jingyi Liu; Hongjun Chen (Virus Genes, 2023)

The optimal speed model based on minimum temporal and spatial energy consumption - Bin Sun; Qijun Zhang; Chao Zou; Ning Wei; Zhenyu Jia; Zhong Wu; Hongjun Mao; Yi Zhang (Environmental Science and Pollution Research, 2023)

Reveal the major factors controlling quinolone adsorption on mesoporous carbon: Batch experiment, DFT calculation, MD simulation, and machine learning modeling - Hongjun Zhao; Yitao Lyu; Jingrun Hu; Min Li; Huan Chen; Yi Jiang; Moran Tang; Yang Wu; Weiling Sun (Chemical Engineering Journal, 2023)

Simultaneous adsorption and biodegradation of polychlorinated biphenyls using resuscitated strain Streptococcus sp. SPC0 immobilized in polyvinyl alcohol‑sodium alginate - Qihua Lin; Jiayan Ding; Yingying Yang; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Science of The Total Environment, 2023)

A novel strategy for enhancing bioremediation of polychlorinated biphenyl-contaminated soil with resuscitation promoting factor and resuscitated strain - Xinru Zhou; Shusheng Zhang; Rui Wang; Zijing An; Faqian Sun; Chaofeng Shen; Hongjun Lin; Xiaomei Su (Journal of Hazardous Materials, 2023)

Impacts of heatwaves and cold spells on glaucoma in rural China: a national cross-sectional study - Ai Zhang; Qihua Wang; Xueli Yang; Yuanyuan Liu; Jiayu He; Anqi Shan; Naixiu Sun; Qianfeng Liu; Baoqun Yao; Fengchao Liang; Ze Yang; Xiaochang Yan; et al. (Environmental Science and Pollution Research, 2023)
China faces increasing health risks from climate change. The structure and function of the eye and vision were affected by extreme heat and cold. The study aimed to evaluate the impacts of heatwaves and cold spells on glaucoma. A national cross-sectional study of the Rural Epidemiology for Glaucoma (REG-China) was conducted in ten provinces of China, and 36,081 adults aged 40 years or more were included. Glaucoma signs were assessed via a standard examination. A total of 15 heatwave definitions, based on intensity (95th to 99th percentiles of temperature distribution) and duration (≥2 days, 3 days, and 4 days), were used to quantify heatwave effects, and 6 cold spell definitions were defined based on threshold temperature percentile (5th and 10th) and duration (3 days, 5 days, and 9 days). Multivariable-adjusted logistic regression models paired with interaction analysis were performed to investigate the impacts of heatwaves and cold spells on glaucoma, and the dose-response relationships were assessed using a restricted cubic spline (RCS) model. Subgroup analysis was conducted stratified by gender, age, smoking status, occupation, and family history of glaucoma. The overall prevalence of glaucoma was 2.1% (95% CI 1.94–2.25%). Higher heatwaves were significantly correlated with higher OR of glaucoma, with the OR (95% CI) ranging from 1.014 (1.009, 1.018) to 1.090 (1.065, 1.115) by different definitions. Glaucoma was affected by heatwaves more strongly than by cold spells. The effects of both heatwaves and cold spells were higher in males than females and in smokers than nonsmokers. These results of the present study evoked the attention of prospective research to elucidate the relationship between extreme temperatures and eye diseases.

Evaluating traffic emission control policies based on large-scale and real-time data: A case study in central China - Chao Zou; Lin Wu; Yanan Wang; Shida Sun; Ning Wei; Bin Sun; Jingwei Ni; Jing He; Qijun Zhang; Jianfei Peng; Hongjun Mao (Science of The Total Environment, 2023)

Comparison of CO2, NOx, and VOCs emissions between CNG and E10 fueled light-duty vehicles - Zongyan Lv; Lin Wu; Chao Ma; Luna Sun; Jianfei Peng; Lei Yang; Ning Wei; Qijun Zhang; Hongjun Mao (Science of The Total Environment, 2023)

Multi-omics analysis reveals copper-induced growth inhibition mechanisms of earthworm (Eisenia fetida) - Yanliang Zhang; Jinqi Zhao; Na Sa; Chenyu Huang; Wenyu Yu; Tianxiao Ma; Hongjun Yang; Fang Ma; Siqi Sun; Chaochun Tang; Weiguo Sang (Environmental Pollution, 2023)

Tunnel measurements reveal significant reduction in traffic-related light-absorbing aerosol emissions in China - Chung Song Ho; Jianfei Peng; Zongyan Lv; Bin Sun; Lei Yang; Jinsheng Zhang; Jiliang Guo; Qijun Zhang; Zhuofei Du; Hongjun Mao (Science of The Total Environment, 2023)

Physically separated soil organic matter pools as indicators of carbon and nitrogen change under long-term fertilization in a Chinese Mollisol - Adnan Mustafa; Qudsia Saeed; Mohammad Tahsin Karimi Nezhad; Sun Nan; Gao Hongjun; Zhu Ping; Muhammad Naveed; Xu Minggang; Avelino Nú nez-Delgado (Environmental Research, 2023)

Helical configuration channels boost performance in anion exchange membranes - Yang Zhang; Fan Zhang; Yiwen Chen; Lixuan Sun; Chengpeng Wei; Huaqing Zhang; Hongjun Zhang; Bangjiao Ye; Liang Wu; Xiaolin Ge; Tongwen Xu (Chemical Engineering Journal, 2023)

Source apportionment of VOCs based on photochemical loss in summer at a suburban site in Beijing - Yajun Wu; Xiaolong Fan; Yan Liu; Jingqiao Zhang; Han Wang; Luna Sun; Tiange Fang; Hongjun Mao; Jun Hu; Lin Wu; Jianfei Peng; Shulan Wang (Atmospheric Environment, 2023)

Multi-Objective Optimization of Bioresorbable Magnesium Alloy Stent by Kriging Surrogate Model - Hongjun Wang; Li Jiao; Jie Sun; Pei Yan; Xibin Wang; Tianyang Qiu (Cardiovascular Engineering and Technology, 2022)

Microbial residues as the nexus transforming inorganic carbon to organic carbon in coastal saline soils - Pengshuai Shao; Tian Li; Kaikai Dong; Hongjun Yang; Jingkuan Sun (Soil Ecology Letters, 2022)

Review and prospect of research on road traffic flow energy model - Bin Sun; Qijun Zhang; Chao Zou; Hui Tong; Ning Wei; Zhenyu Jia; Hongjun Mao (Environmental Science and Pollution Research, 2022)

Three-Dimensional Direct Numerical Simulations of a Yawed Square Cylinder in Steady Flow - Xiaofan Lou; Chenlin Sun; Hongyi Jiang; Hongjun Zhu; Hongwei An; Tongming Zhou (Journal of Marine Science and Engineering, 2022)
The effects of yaw angle on wake characteristics of a stationary square cylinder were investigated in terms of the hydrodynamic forces, the vortex shedding frequency, and the vortical structures using direct numerical simulations (DNS) at a Reynolds number of 1000. In total, four yaw angles, namely, α = 0°, 15°, 30°, and 45°, were considered. The three-dimensional (3D) Navier–Stokes equations were solved directly using the finite volume method in OpenFOAM. It was found that the first-order statistics of the drag coefficient and the Strouhal number satisfied the independence principle (IP) closely. However, the second-order statistics of the drag and lift coefficients deviated apparently from the IP for α ≥ 25°. The iso-surfaces of the spanwise vorticity gradually disorganized and the magnitudes of the spanwise vorticity contour decreased as the yaw angle α was increased from 0° to 45°. By contrast, the streamwise vorticity iso-surfaces were found to become more organized and the magnitudes of the spanwise velocity contour became larger as a result of the increase in yaw angle, indicating the impairment of the quasi-two-dimensionality and the enhancement of the three-dimensionality of the wake flow. Extensive comparisons were also made with previous DNS results for a yawed circular cylinder, and both similarities and differences between these two kinds of cylinder wakes are discussed.

Estimation of the critical hydraulic gradient of coarse soil using the DEM-CFD coupling method - Hongyue Sun; Zekun Zhang; Xiaohong Wang; Jingyong Wang; Hongjun Jiang; Jiayi Shen (Arabian Journal of Geosciences, 2022)

How habitat heterogeneity shapes bacterial and protistan communities in temperate coastal areas near estuaries - Zelong Zhao; Hongjun Li; Yi Sun; Kuishuang Shao; Xiaocheng Wang; Xindong Ma; Anyi Hu; Haikun Zhang; Jinfeng Fan (Environmental Microbiology, 2022)
Summary In this study, we investigated microbial communities (bacteria and protist) in two coastal areas near the estuaries of the Liaohe (LH) River and Yalujiang (YLJ) River in the Northwestern Pacific Ocean. Due to the existence of Liaodong Peninsula and different levels of urbanization, geographical segregation and significant environmental heterogeneity were observed between these two areas. There were significantly different regional species pools and biogeographic patterns for both bacterial and protistan communities between LH and YLJ coastal areas. Species turnover was the main mechanism driving β‐diversity patterns of both bacterial and protistan communities in each area. In addition, the contributed ratio of nestedness to the β‐diversity patterns was significantly higher for protists compared to bacteria. Variation in regional species pools was found to be the dominant driver of differences of bacterial and protistan communities between the LH and YLJ coastal areas. For a single‐studied area, local community assembly mechanisms, including heterogeneous selection and dispersal limitation, were found to shape the bacterial and protistan communities through calculation of the β‐deviation index. Among them, the relative importance of heterogeneous selection and dispersal limitation on the community assembly varied according to microorganism type and habitat.

Combination of Polyethylene Glycol-Conjugated Urokinase Nanogels and Urokinase for Acute Ischemic Stroke Therapeutic Implications - Ding Nan; Haiqiang Jin; Di Yang; Weiwei Yu; Jingjing Jia; Zemou Yu; Hui Tan; Yongan Sun; Hongjun Hao; Xiaozhong Qu; Yining Huang (Translational Stroke Research, 2021)

Profiling of Serum Exosome MiRNA Reveals the Potential of a MiRNA Panel as Diagnostic Biomarker for Alzheimer’s Disease - Zhiwu Dong; Hongjun Gu; Qiang Guo; Shuang Liang; Jian Xue; Feng Yao; Xianglu Liu; Feifei Li; Huiling Liu; Li Sun; Kewen Zhao (Molecular Neurobiology, 2021)

Distribution and Assessment of Cr, Pb, Ni and Cd in Topsoil of the Modern Yellow River Delta, China - Hongjun Yang; Jingkuan Sun; Jiangbao Xia; Zhanyong Fu; Shuai Cheng; Tian Li; Pengshuai Shao; Kaikai Dong; Jinzhao Ma; Lu Feng (Wetlands, 2021)

A longitudinal study of brain volume changes in rhesus macaque model infected with SIV - Bonan Song; Yunfang Li; Jiaojiao Liu; Haifeng Mi; Dan Liu; Wei Wang; Jun Sun; Yuanyuan Wang; Hongjun Li (Journal of NeuroVirology, 2020)

Magnesium alleviates aluminum toxicity by promoting polar auxin transport and distribution and root alkalization in the root apex in populus - Zhen Zhang; Dunyi Liu; Hongjun Meng; Shengting Li; Shufeng Wang; Zhongchun Xiao; Juanjuan Sun; Longran Chang; Keming Luo; Nannan Li (Plant and Soil, 2020)

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

Physiological, genomic and transcriptomic comparison of two Brassica napus cultivars with contrasting cadmium tolerance - Shufeng Wang; Juanjuan Sun; Shengting Li; Kun Lu; Hongjun Meng; Zhongchun Xiao; Zhen Zhang; Jiana Li; Feng Luo; Nannan Li (Plant and Soil, 2019)

Phytoplankton pigment pattern in the subsurface chlorophyll maximum in the South Java coastal upwelling system, Indonesia - Chunlei Gao; Mingzhu Fu; Hongjun Song; Lei Wang; Qinsheng Wei; Ping Sun; Lin Liu; Xuelei Zhang (Acta Oceanologica Sinica, 2018)

Pm61: a recessive gene for resistance to powdery mildew in wheat landrace Xuxusanyuehuang identified by comparative genomics analysis - Huigai Sun; Jinghuang Hu; Wei Song; Dan Qiu; Lei Cui; Peipei Wu; Hongjun Zhang; Hongwei Liu; Li Yang; Yunfeng Qu; Yahui Li; Teng Li; et al. (Theoretical and Applied Genetics, 2018)

MCP1 triggers monocyte dysfunctions during abnormal osteogenic differentiation of mesenchymal stem cells in ankylosing spondylitis - Zhongyu Xie; Peng Wang; Jinteng Li; Yuxi Li; Shan Wang; Xiaohua Wu; Suhe Sun; Shuizhong Cen; Hongjun Su; Wen Deng; Zhenhua Liu; Yi Ouyang; et al. (Journal of Molecular Medicine, 2017)

Heterosis and combining ability of seven maize germplasm populations - Xiaocong Zhang; Hongjun Yong; Zhiqiang Zhou; Chaoshu Zhang; Ming Lu; Qi Sun; Lin Zhang; Mingshun Li; Degui Zhang; Jianfeng Weng; Zhuanfang Hao; Shihuang Zhang; et al. (Euphytica, 2017)

A pilot fMRI study of the effect of stressful factors on the onset of depression in female patients - Gongying Li; Xiaoyan Ma; Haiman Bian; Xinhai Sun; Ning Zhai; Mengyuan Yao; Hongru Qu; Shengzhang Ji; Hongjun Tian; Chuanjun Zhuo (Brain Imaging and Behavior, 2016)

The expression of Na, K-ATPase in Litopenaeus vannamei under salinity stress - Hongyan Sun; Lvping Zhang; Chunhua Ren; Chang Chen; Sigang Fan; Jian Jun Xia; Hongjun Lin; Chaoqun Hu (Marine Biology Research, 2011)